Expressive Writing as a Tool to Face Quarter-Life Crisis On College Students in Time of Covid-19 Pandemic - Sari, Dhea Intan Puspita (Jurusan PGPAUD FIP UNNES, 2021)
The purpose of this study is to discuss expressive writing as a tool that can be practiced for students in facing the quarter life crisis during the Covid-19 pandemic. The method used in this study is literature study by analysing and studying scientific literature on the topic of the quarter life crisis, expressive writing, and the period of emerging adulthood. Expressive writing is done by writing down emotions and feelings honestly in a span of about 15 minutes and is done consistently to understand what is going on in the individual. The results of this literature study show that expressive writing can be such therapeutic activity and can help students deal with quarter life crises in this pandemic.